EFEKTIVITAS SISTEM ABSENSI MANUAL DALAM MENINGKATKAN DISIPLIN SISWA DI MI. MUHAMMADIYAH ROMANG LOMPOA - Haerana; Siti Inganah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the manual attendance system used at MI Muhammadiyah Romang Lompoa in improving student attendance discipline. Discipline is an important foundation in character building and student academic success, where the attendance system serves as a record and primary control tool. The method used is quantitative descriptive research using a survey approach, involving all students and teachers involved in recording attendance. Data collection was carried out through observation of attendance procedures, documentation of attendance data (lateness, permission, absenteeism) for the past semester, and questionnaires to students and teachers. The results of the study indicate that the manual attendance system has a fairly high (or moderate) effectiveness in reducing the number of unexcused absences (alpa), but its effectiveness is less than optimal in overcoming the problem of lateness. Factors that support effectiveness are teacher consistency in recording and verifying attendance and the presence of direct follow-up from the homeroom teacher. Meanwhile, the main inhibiting factors are human error in recording and the lack of novelty/technology elements that make the process feel less binding for some students. It was concluded that the manual attendance system was effective as a basic recording tool, but required strengthening in the form of a firmer and more consistent reward and punishment mechanism to achieve the maximum level of discipline, especially in terms of punctuality.